THE INFLUENCE OF LOCAL POWERS IN THE FIRST ASTUR EXPANSION (9 TH AND 10 TH CENTURY). - Mínguez Fernández, José María (Revista de Historia Social y de las Mentalidades, 2024)
The swift Astur expansion between the Cantabrian range and the Duero river is explained in this article from the perspective of the persistence of population and of some kind of political organization, no matter how rudimentary. The defense of this thesis is based on the proven fact of an Astur occupation of several settlements of the Duero plateau, which had been in the more or less remote past centers of social control or of military organization and that, before their conquest, would turn to be the seat of local powers with authority over small districts and that had little or no articulation between themselves. Deeply knowing the territory and with government experience, they would end up accepting the supremacy of Astur kings. This acceptance would be rewarded by their integration in the kingdom Ìs new aristocracy alongside the old Astur aristocracy and the ecclesiastical elite of bishops and abbots.